Examining consumers attitude towards E-wallet utilization as a payment method using technology acceptance model: A perspective from young generations in Nueva Ecija, Philippines - Leyesa, Marlon; S. De Jesus, Fhrizz; De Jesus, Crisanto; Gerald A. Quijano, Atty; Agustin, Noel (Edelweiss Applied Science and Technology, 2024)
This study aims to provide valuable insights into how consumers interact with e-wallets in order to understand their behaviors and preferences. This perspective and behavior can help businesses and institutions better understand consumer behavior and develop strategies to increase e-wallet adoption. This research study is descriptive in nature. The researchers utilized frequency, percentage, weighted mean, and pearson R as statistical treatment. According to the findings, majority of respondents stated that Information Privacy is the most common and most encountered problem related to their use of e-wallets, while few reported the fewest, which were Unauthorized Application Updates. The statement implies that the majority of respondents were concerned about their information’s security and safety. According to respondents, fear stems from concerns about others gaining unauthorized access, data breaches, or the misuse of sensitive information. Conduct interviews and surveys in your community to find out why people aren’t using e-wallets. The researchers recommended implementing training programs on e-wallet usage to educate the community through focused campaigns, enhancing the usability and accessibility of the application for ongoing enhancement.